1994
DOI: 10.1080/01688639408402651
|View full text |Cite
|
Sign up to set email alerts
|

Mirror movements in normal adult subjects

Abstract: Intensity of mirror movements occurring under specific task conditions in normal adults was investigated using a finger flexion task. Subjects were asked to sustain target pressures using different fingers. Greater pressures of mirror movement were recorded when the weaker, small finger of either hand performed the task. The target pressure which subjects were asked to sustain did not influence the amount of mirror movement exhibited by either males or females, even though higher target forces required a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 25 publications
7
78
2
Order By: Relevance
“…The finding of comparable inhibition of iM1 for movements of both hands suggests that the higher incidence of mirroring with left than right hand movements (Liepert, Dettmers, Terborg, & Weiller, 2001;Armatas, Summers, & Bradshaw, 1994;Todor & Lazarus, 1986) cannot be accounted for by a differential efficiency of IHIi. Rather, more frequent mirroring with left hand movements might relate to an increased contribution of the ipsilateral left premotor cortex when movements are performed with the nondominant hand (Verstynen et al, 2005;Haaland et al, 2004;Cramer et al, 1999;Kim, Ashe, Hendrich, et al, 1993).…”
Section: Movement-related Interhemispheric Inhibition Targeting Primamentioning
confidence: 75%
“…The finding of comparable inhibition of iM1 for movements of both hands suggests that the higher incidence of mirroring with left than right hand movements (Liepert, Dettmers, Terborg, & Weiller, 2001;Armatas, Summers, & Bradshaw, 1994;Todor & Lazarus, 1986) cannot be accounted for by a differential efficiency of IHIi. Rather, more frequent mirroring with left hand movements might relate to an increased contribution of the ipsilateral left premotor cortex when movements are performed with the nondominant hand (Verstynen et al, 2005;Haaland et al, 2004;Cramer et al, 1999;Kim, Ashe, Hendrich, et al, 1993).…”
Section: Movement-related Interhemispheric Inhibition Targeting Primamentioning
confidence: 75%
“…This relay probably includes multiple (active) levels along 107 the neuroaxis-like ipsilateral oligosynaptic pathways and corticoreticulo-or corticopropriospinal projections (Ziemann et al 1999;Leocani et al 2000). Irrespective of the exact location of the postulated inhibitory mechanisms, the proposed model indicates that an eventual loss of inhibition may result in instabilities and phase transitions or, more generally, unintended motor output (Armatas et al 1994;Leinsinger et al 1997;Daffertshofer et al 1999). 4 Against this background, modeling neural cross-talk and ipsilateral control mechanisms during manual performance requires two M1s and additional cortical mediators; here the latter were summarized as premotor areas.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of such findings, suggested that even simple voluntary movements cause exigencies prompting the motor system to 102 respond by increasing not only the regional activation but also the information flow between hemispheres. In particular, links between bilateral motor areas may play an important role in suppressing mirror movements, that is, associated movements in arms or hands not intended to move (Armatas et al 1994;Leinsinger et al 1997;Daffertshofer et al 1999), implying that those connections are effectively inhibitory. The existence of interhemispheric inhibition has indeed been demonstrated by applying transcranial magnetic (conditioning) stimuli over the motor cortex in one hemisphere, which turned out to affect responses to stimuli over the motor cortex in the other hemisphere (Ferbert et al 1992;Meyer et al 1995;Boroojerdi et al 1996;Ikeda et al 2000;Hanajima et al 2001;Meyer-Lindenberg et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Mirror movements typically occur in healthy adults only during sustained effortful and fatiguing voluntary contractions (Cernacek 1961;Todor and Lazarus 1986;Dimitrijevic et al 1992;Armatas et al 1994). Such effort-induced mirror movements indicate a reduced ability of the CNS to selectively control individual muscles.…”
Section: Introductionmentioning
confidence: 99%